2006
DOI: 10.1107/s160053680600420x
|View full text |Cite
|
Sign up to set email alerts
|

Aqua(dipicolinato-κ3O,N,O′)(1,10-phenanthroline-κ2N,N′)zinc(II) monohydrate

Abstract: The title compound, [Zn(C7H3NO4)(C12H8N2)(H2O)]·H2O, is isostructural with the manganese(II) analogue. The Zn atom is coordinated by a tridentate dipicolinate dianion, a bidentate 1,10‐phenanthroline mol­ecule and a water mol­ecule, resulting in a substanti­ally distorted ZnO3N3 octa­hedral grouping. The crystal packing is consolidated by O—H⋯O hydrogen bonds and probable π–π stacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Bond lengths and angles are comparable with those in similar structures (Tabatabaee et al, 2009;MacDonald et al, 2000;Aghabozorg et al, 2008;Harrison et al, 2006). Recently, our group reported a similar compound with Mn(II) as a metal center which has the same stochiometery as the title compound (Eshtiagh-Hosseini, Mirzaei, Eydizadeh et al, 2011 2).…”
Section: S1 Commentsupporting
confidence: 75%
“…Bond lengths and angles are comparable with those in similar structures (Tabatabaee et al, 2009;MacDonald et al, 2000;Aghabozorg et al, 2008;Harrison et al, 2006). Recently, our group reported a similar compound with Mn(II) as a metal center which has the same stochiometery as the title compound (Eshtiagh-Hosseini, Mirzaei, Eydizadeh et al, 2011 2).…”
Section: S1 Commentsupporting
confidence: 75%
“…It functions as the active site of hydrolytic enzymes, such as carboxypeptidase and carbonic anhydrase, where it is in a hard-donor coordination environment of nitrogen and oxygen (Lipscomb & Strä ter, 1996;Bertini et al, 1994). It also has long been recognized as an important cofactor in biological molecules, either as a structural template in protein folding or as a Lewis acid catalyst that can readily adopt four-, five-or six-coordination (Harrison et al, 2006;Tirosh et al, 2005;Musie et al, 2004;Vallee & Auld, 1993). Recent reports have suggested that zinc is able to play a catalytic role in the activation of thiols as nucleophiles at physiological pH (Wilker & Lippard, 1997;Myers et al, 1993).…”
Section: Commentmentioning
confidence: 99%
“…Zinc is the second most abundant transition metal in biology and functions as the active site of hydrolytic enzymes, such as carboxypeptidase and carbonic anhydrase, where it is in a hard donor coordination of nitrogen and oxygen (Lipscomb & Strä ter, 1996;Bertini et al, 1994). Zinc has long been recognized as an important co-factor in biological molecules, either as a structural template in protein folding or as a Lewis acid catalyst that can readily adopt four-, five-or six-coordination (Harrison et al, 2006;Tirosh et al, 2005;Musie et al, 2004;Vallee & Auld, 1993). Recent reports have suggested that zinc is able to play a catalytic role in the activation of thiols as nucleophiles at physiological pH (Wilker & Lippard, 1997;Myers et al, 1993).…”
Section: Commentmentioning
confidence: 99%